IMF Staff papers : Volume 4 No. 1. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1954)
This paper discusses short-range forecasting of US imports. At first sight the movement of dollar acceptances for imports into the United States might reasonably be expected to indicate what the movement of imports would be in some succeeding period. Both gross national product (GNP) and national income have been generally considered the most important determinants of US imports, and many regression relations between imports and GNP, or national income, have been calculated in the literature on this subject. An examination of quarterly data, however, reveals practically identical major turning points in GNP, in national income, and in total imports, so that neither lagged GNP nor lagged national income can be used to indicate these turnings. Variations in new orders placed with manufacturers might be expected, a priori, to be closely associated with subsequent variations in imports. Viewed in the light of these considerations, the superiority of the new orders relation over the autoregressive relation is seen to be much greater than is suggested by the correlation coefficients alone.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet